Visual guidelines of editorial design for a dictionary of graphic design and typography - Álvarez Sandi, Laura; Quindós González, Tania (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The aim of this study is to analyse the macro and microtypographic variables that condition the editorial quality and accessibility of the linguistic content of a dictionary specialized in graphic design and typography. Using a common file with syntactic, semantic and functional parameters, we studied 20 printed and digital dictionaries published between 1979 and 2022, according to criteria marked by their exemplary value and graphic quality. A possible typology of these dictionaries is proposed, as well as guidelines for the editorial design and didactic performance of this type of publications, in their final stage of digital and printed implementation.